Simplified absorption line selection methods for water absorption thermometry around 2 µm. (July 2023) - Tao, Mengmeng; Wang, Yamin; Wu, Haolong; Ye, Jingfeng; Ye, Xisheng; Chen, Weibiao
Highlights: Three simplified line-selection methods are proposed. And, compared with the conventional line-selection method, these three simplified methods provide comparable temperature precision, but with a much faster selection speed. Line selection regarding the emerging 2 µm laser sources in absorption thermometry applications is investigated, discussed and evaluated covering a wide temperature range from 400 K to 2000 K. Abstract: Line-selection is of vital importance for absorption spectroscopy based thermometry. Up to now, various analytical and numerical line-selection methods have been developed to tackle this issue. Here, concerning the numerical line-selection of water around 2 µm, the conventional method based on the frequency-dependent lower-state energy is simplified through pre-filtering of the candidate absorption lines. As a result, the previous thousands of candidate lines is greatly reduced to a few dozen. With reduced libraries, three simplified line-selection methods are proposed. Line selection results of the simplified methods in the investigated wavelength span from 1800 nm to 1900 nm are discussed and evaluated covering a wide temperature range from 400 K to 2000 K. Comparisons with the conventional method demonstrates that, these three simplified methods provide comparable temperature precision, but with a much faster selection speed.